(untitled) (Journal of Partial Differential Equations, 2020)
Using the polygonal approximations method, we construct the global approximate solution of the initial boundary value problem (1.1)-(1.3) for the scalar nonconvex conservation law, and prove its convergence. The crux of this work is to clarify the behavior of the approximations on the boundary x = 0.